ON THE MAEOTIAN GENUS COELACANTHIA ANDRUSOV (RISSOIDAE, GASTROPODA) - Iljina L.B. (My University, 2001)
The revised diagnosis of the genus Coelacanthia is given for the first time. Special attention was paid to the aperture structure of C. quadrispinosa. The similarity of the Maeotian Coelacanthia and Karaganian Archaschenia is shown to be homoeomorphic.
Keywords: Coelacanthia